Youth and Jobs in Rural Africa: Beyond Stylized Facts - Thurlow, James; Mueller, Valerie (2020)
James Thurlow and Valerie Mueller BOOK LAUNCH Youth and Jobs in Rural Africa: Beyond Stylized Facts Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets JAN 21, 2020 - 12:15 PM TO 01:15 PM EST